Angle of Electron Winding - Gregory A., Korablev (International Journal Of Chemistry, Mathematics And Physics(IJCMP), 2017)
It is demonstrated that corpuscular interactions flow along the potential gradient (principle of adding reciprocals of energies), and wave processes – against the potential gradient (principle of algebraic addition of energies).